2014
DOI: 10.1088/0004-637x/794/2/132
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Effects in Hot Jupiter Atmospheres

Abstract: We present magnetohydrodynamic simulations of the atmospheres of hot Jupiters ranging in temperature from 1100 to 1800 K. Magnetic effects are negligible in atmospheres with temperatures 1400 K. At higher temperatures winds are variable and, in many cases, mean equatorial flows can become westward, opposite to their hydrodynamic counterparts. Ohmic dissipation peaks at temperatures ∼1500-1600 K, depending on field strength, with maximum values ∼10 18 W at 10 bars, substantially lower than previous estimates. B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
198
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(211 citation statements)
references
References 52 publications
12
198
1
Order By: Relevance
“…Further theoretical work could help reduce these uncertainties. Our result that Lorentz forces are potentially unimportant for HD 189733b but may be important for HD 209458b therefore agrees with previous estimates that magnetic drag could become significant at T 1400 K eq  (Menou 2012;Rogers & Komacek 2014). In contrast to magnetic drag, we find that shear instabilities are a plausible mechanism to match the observations of both planets ( Figure 5, bottom panel).…”
Section: Evaluating Drag Mechanisms With Observationssupporting
confidence: 92%
See 1 more Smart Citation
“…Further theoretical work could help reduce these uncertainties. Our result that Lorentz forces are potentially unimportant for HD 189733b but may be important for HD 209458b therefore agrees with previous estimates that magnetic drag could become significant at T 1400 K eq  (Menou 2012;Rogers & Komacek 2014). In contrast to magnetic drag, we find that shear instabilities are a plausible mechanism to match the observations of both planets ( Figure 5, bottom panel).…”
Section: Evaluating Drag Mechanisms With Observationssupporting
confidence: 92%
“…Note that Equation (14) does not include induced atmospheric fields. In strongly ionized atmospheres, induced fields can be significant (Rogers & Showman 2014;Rogers & Komacek 2014;Rogers & McElwaine 2017), which means winds could decrease faster with equilibrium temperature than implied by Equation (14).…”
Section: Evaluating Drag Mechanisms With Observationsmentioning
confidence: 99%
“…As in Perez-Becker & Showman (2013), they showed that the combined effects of increasing relative efficacy of radiative cooling and increasing drag strength can explain the increase in dayside-nightside temperature contrast with increasing equilibrium temperature, as both mechanisms damp wave adjustment processes. This drag is likely due to either Lorentz forces in an ionized atmosphere threaded by a dipolar magnetic field (Perna et al 2010;Batygin et al 2013;Rauscher & Menou 2013;Rogers & Komacek 2014;Rogers & Showman 2014) or smallscale instabilities (Li & Goodman 2010;Youdin & Mitchell 2010;Fromang et al 2016), including shocks, which largely are expected to occur on the dayside of the planet (Heng 2012;Fromang et al 2016). However, Komacek & Showman (2016) found that drag only affects dayside-nightside temperature differences if it occurs on a characteristic timescale much shorter than the rotation period of the planet.…”
Section: Introductionmentioning
confidence: 99%
“…More realistically, the morphology of the equatorial jet may not lead to a perfect hemispherical separation of aerosol versusnon-aerosol-dominated segments of the terminator. For example, magnetic effects, which are expected to influence the most highly irradiated planets and are typically not self-consistently included in GCMs, could alter the magnitude and morphology of atmospheric winds (Rauscher & Menou 2013;Rogers & Komacek 2014). Additionally, GCMs that include cloud tracer particles qualitatively predict a non-uniform spatial distribution of aerosols in exoplanet atmospheres (Parmentier et al 2013;Charnay et al 2015).…”
Section: Resultsmentioning
confidence: 99%